Impact of Patient Education on Quality of Life of Asthma Patients in an Indian Tertiary Care Hospital - P, Hiral; Rani R.H, Shobha; P, Nalini; S, Ramjan; CS, Sunitha (Indian Journal of Pharmacy Practice)
Background: The overall burden of asthma in India is estimated at more than 15 million patients. It can place considerable limitations on the physical, emotional, social and professional lives of patients, with substantial negative impact on quality of life (QOL). Literature provides evidence that clinical pharmacists have contributed to patient care through education which enhances the feasibility of asthma self-management. Objectives: To study the impact of patient education provided by the clinical pharmacist regarding asthma, self-management and inhaler technique in improving the quality of life of asthma patients in a South Indian tertiary care hospital. Methodology: The study was randomized, comparative and intervention based with 92 patients who were randomized into intervention (49 patients) and control st rd th groups (43 patients). After the enrolment period of 1 month (Baseline), three follow-ups were carried out at the intervals of 1 , 3 and 5 month. The parameters measured in this study included peak expiratory flow rate (PEFR), inhalation technique, QOL and asthma self-management. During the follow-ups, intervention group received verbal and written education on asthma and inhaler techniques for self-management along with routine medical consultation whereas, the control group received only routine medical consultation during the follow-ups and education on asthma at the end of the study. Results:At the baseline, mean PEFR value was 186.78 mL/sec in intervention group and 187.26 mL/sec in control group. Asignificant difference was noted at 2 rd nd rd (P=0.006) and 3 (P=0.000) follow-up. Intervention group showed a significant improvement in inhalation technique at 2 (P=0.000) and 3 (P=0.000) follow-up. At the end of the study, QOL of patients in the intervention group improved compared to control group. Significant improvement (P=0.000) was noted in Asthma SelfManagement Questionnaire (ASMQ) score in the intervention group. Conclusion: Results of this study shows that clinical pharmacist's educational interventions had a positive impact on the understanding and self-management of asthma patients which helps in improving their health and quality of life.
Keywords: Asthma; ASMQ; Patient education; Quality of Life; SF-36